Of Valuable Agricultural Characters In F1 Plants Of Medium Fiber Cotton Gen Collection Lines (Texas Journal of Multidisciplinary Studies, 2023)
In the article Inheritance of valuable husbandry traits was determined in F1 plants of medium fiber cotton gene collection lines